2011
DOI: 10.1136/jramc-157-01-08
|View full text |Cite
|
Sign up to set email alerts
|

Energy at High Altitude

Abstract: For the military doctor, an understanding of the metabolic effects of high altitude (HA) exposure is highly relevant. This review examines the acute metabolic challenge and subsequent changes in nutritional homeostasis that occur when troops deploy rapidly to HA. Key factors that impact on metabolism include the hypoxic-hypobaric environment, physical exercise and diet. Expected metabolic changes include augmentation of basal metabolic rate (BMR), decreased availability of oxygen in peripheral metabolic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…given the higher RER that was shown during HYP exercise in the present study, as well as prior work reporting increased energy expenditure during work at high altitude (Hill et al 2011) and IL-6's known role as an extracellular energy sensor (Pedersen 2012), this might also reflect HYP promoting greater IL-6 release from skeletal muscle on account of the greater cellular energy demand.…”
Section: Limitationssupporting
confidence: 63%
“…given the higher RER that was shown during HYP exercise in the present study, as well as prior work reporting increased energy expenditure during work at high altitude (Hill et al 2011) and IL-6's known role as an extracellular energy sensor (Pedersen 2012), this might also reflect HYP promoting greater IL-6 release from skeletal muscle on account of the greater cellular energy demand.…”
Section: Limitationssupporting
confidence: 63%
“…Corroborating the results of Moon et al [31], we observed no significant difference in VO 2 between hypoxic and normoxic conditions during submaximal exercise; this is likely because the exercise intensity was fixed at a constant level across simulated environment conditions, resulting in the expenditure of same amount of energy. In addition, Hill et al [35] and Mazzeo [36] reported that the lack of difference in VO 2 during submaximal exercise between both environmental conditions is due to an increase in VE, HR, and CO because of acute hypoxic conditions. Furthermore, exercise under hypoxic conditions results in a decrease in the partial pressure of oxygen in the arterial blood, which leads to metabolic acidosis due to increase in ATP synthesis by the anaerobic metabolic process, increase in hydrogen ion, and decrease in pH [37].…”
Section: Discussionmentioning
confidence: 99%
“…▸  Protocol 624, appetite responses during a HA expedition : very little is known about the underlying mechanisms regarding the anorexia and nausea suffered at HA, a topic previously reviewed in this journal 12. Reductions in appetite contribute to the degradation that ultimately impairs performance at HA.…”
Section: Methodsmentioning
confidence: 99%